2010
DOI: 10.5352/jls.2010.20.11.1603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fucus evanescens Fucoidan on Expression of Matrix Metalloproteinase-1 Promoter, mRNA, Protein and Signal Pathway

Abstract: Fucoidans are sulfated fucosylated polymers from the cell wall of brown algae. We assessed the effects of Fucus evanescens fucoidan on ultraviolet-B (UVB)-induced expression of matrix metalloproteinase-1 (MMP-1) protein, mRNA, and promoter, and the phosphorylation of mitogen-activated protein kinases in vitro using an immortalized human keratinocyte cell line. Pretreatment with 10 and 100 μg/ml fucoidan significantly inhibited UVB-induced MMP-1 protein, mRNA and promoter activity, compared to UVB irradiation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Other less documented benefits described for Fucus spp. fucoidans include anti-obesity [ 92 ], anti-photoaging [ 127 , 128 ] and antibacterial [ 129 , 130 ].…”
Section: Nutrient Composition Of Fucus Sppmentioning
confidence: 99%
“…Other less documented benefits described for Fucus spp. fucoidans include anti-obesity [ 92 ], anti-photoaging [ 127 , 128 ] and antibacterial [ 129 , 130 ].…”
Section: Nutrient Composition Of Fucus Sppmentioning
confidence: 99%
“…Previous studies have reported that fucoidan isolated from S. japonica has a variety of bioactivities, such as neuroprotective, anti-inflammation, antioxidant, antiviral, immunomodulatory, atherosclerosis mitigation and anticoagulant activities [16][17][18][19][20][21]. Some researchers have investigated the anti-UVB ability of fucoidan from brown seaweed, such as Costaria costata, Fucus evanescens and Undaria pinnatifida [22][23][24]; however, this is the first study on the anti-UVB activities of fucoidan extracted from S. japonica.…”
Section: Introductionmentioning
confidence: 98%
“…The photoprotective activity of fucoidan has been studied using UVB irradiated HaCaT and human foreskin fibroblast (HS 68) cells, zebrafish, and in vivo models [ 19 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The earliest study on the photoprotective activity of fucoidan was carried out by Kim et al in 2008.…”
Section: Seaweed Compounds As Potential Sources Of Anti-photoagingmentioning
confidence: 99%
“…The number, extraction, purification, and characterization of anti-photoaging compounds from marine sources are high and competitive compared to other marine floras such as sea grass, mangroves, and marine faunas (i.e., teripang or sea cucumber, sea star, sea urchin, and more). Furthermore, seaweed polysaccharides including fucoidan, laminarin, and carrageenan ( Figure 1 ) showed potential anti-photoaging properties which were mediated by intra-cellular ROS scavenging activity in UV irradiated cells and in vivo models [ 16 , 17 , 18 , 19 ]. Other seaweed-derived materials such as mycosporine like amino acids (MAAs) are well known as the most potential natural UVA-absorbing molecules [ 13 ].…”
Section: Introductionmentioning
confidence: 99%